Religious Studies Beyond the Discipline: A Manifesto on Earning and Awarding a Ph.D. - Aghapour, Andrew Ali (Bulletin for the study of religion, 2022)
Relying on the collaborative input from doctoral graduates in the study of religion who have gone on to successful careers outside of academia, this essay offers a critique of the field for not adapting far quicker to the changing economic conditions of higher education over recent decades but also provides a variety of practical suggestions for how programs in our field can make tactical and substantive changes to better prepare graduate students for a far wider variety of professional futures, inasmuch as we all know that few, at least for the foreseeable future, will ever be hired as tenure-track faculty members.